Ecotype-specific effects of fungal endophytes on germination responses of seeds of the South American wild forage grass Bromus auleticus - Stefanoni Rubio, Pablo Jose (2021)
Bromus auleticus is a winter wild species with promissory characteristics for domestication as forage that inhabits temperate-warm grasslands from a wide region from South America. Populations from regions with different environmental conditions are considered as ecotypes and are associated with different seedborne Epichloë fungal endophytes. Association with Epichloë provides B. auleticus with increased growth capacity and resistance against pathogens. The seeds mature at the end of spring and germinate in autumn, remaining dormant during wet and warm summer. As the persistence of Epichloë endophytes in the seed is highly sensitive to temperature and humidity, we studied how the endophytes modulate seed germination in response to these factors in two B. auleticus ecotypes named La Pampa (LP) and El Palmar (EP). We also studied how environmental factors during germination affect endophyte survival. In the LP ecotype, adapted to coldest temperatures in autumn, Epichloë improved final germination under alternating temperatures, but had no effects on germination inhibition imposed by low water availability. In the EP ecotype, adapted to warm humid summer and autumn, the endophyte promoted germination at constant 25°C and alternating 15/25°C temperatures, and prevented germination at low water potentials. At 30°C, seed germination was inhibited and whereas seeds remained viable, endophyte survival was significantly lowered. The effect of Epichloë on B. auleticus seed germination was ecotype-specific: promoting germination at alternating temperatures in La Pampa ecotype or at high temperatures in El Palmar ecotype, while inhibiting it at low water availabilities, could be an endophyte-mediated ecotypic strategy minimising endophyte mortality and increasing seedling establishment.